2008
DOI: 10.1002/pits.20348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reading attitude on reading achievement: A test of the temporal‐interaction model

Abstract: Despite widespread efforts to prevent reading problems and an abundance of research about best practices in remediating reading skills deÞcits, reading continues to be exceptionally difÞcult for many students. Researchers have become interested in investigating the degree to which affective factors such as reading attitude relates to reading performance. In the current study, 76 fourthgrade students were administered Curriculum-Based Measurement tasks in reading (R-CBM) and the Elementary Reading Attitude Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 25 publications
6
57
1
9
Order By: Relevance
“…In a regression study, Martinez et al (2008) also demonstrated that reading attitude significantly predicted reading achievement (β = 0.22). Indeed, the aforementioned researchers have suggested that the role of attitude should not be neglected in the process of foreign language learning.…”
mentioning
confidence: 86%
“…In a regression study, Martinez et al (2008) also demonstrated that reading attitude significantly predicted reading achievement (β = 0.22). Indeed, the aforementioned researchers have suggested that the role of attitude should not be neglected in the process of foreign language learning.…”
mentioning
confidence: 86%
“…Bu dış faktörlerin yanı sıra okumaya karşı duyulan motivasyon, ilgi, merak, öz yeterlilik (Black, 2006;Forget 2004;Richardson ve Morgan, 2003;Putman ve Walker, 2010); okumaya stratejileri (Forget, 2004); okumaya ilişkin olumlu ve olumsuz duygulardaki süreklilik ve değişim (Kush ve Watkins, 1996;McKenna, Kear ve Ellsworth, 1995); öğrencinin sahip olduğu amaç, değer ve inançları da kapsayan içsel faktörler de okumaya yönelik tutumu etkilemektedir (Bokhorst-Heng ve Pereira, 2008;Ho ve Guthrie, 2013;McGeown vd., 2015;Schiefele, Schaffner, Moller ve Wigfield, 2012). Okuma becerilerini doğrudan etkileyen okumaya ilişki tutum (Conlon, Zimmer-Gembeck, Creed ve Tucker, 2006;Martinez, Aricak ve Jewell, 2008;Morgan ve Fuchs, 2007;Tuckman, 1999) öğretim sürecinde öğrencilerin değerleri, benlik saygıları ve akademik gelişimleri hakkında da önemli ipuçları vermektedir (Kaniuka, 2010). Tutum bu yönüyle de öğrencinin gelişimsel sürecinde önemli bir yere sahip olmakla birlikte okuma eyleminin önemli bir duyuşsal değişkeni olarak öğrencilerin akademik yaşamlarında da önemli etkilere sahiptir.…”
Section: Okuma Kaygısıunclassified
“…Para a escala toda, o Alfa de Cronbach foi semelhante aos das investigações de McKenna e Kear (1990), Martínez et al (2008), Thornton (2008), Kruzicki (2009) Constatou-se que, num período de dois anos, a ERAS-Br apresentou coeficientes de estabilidade que variaram entre suficientes (Total, ALR e ALAG) e bons (ALA e ALAA). Ao efetuar um estudo de teste-reteste da ERAS com intervalo de um ano, Kush et al (1995) identificaram um coeficiente (0,43) que foi classificado como "estável".…”
Section: Erasunclassified